Single photon ionization of methyl isocyanide and the subsequent unimolecular decomposition of its cation: experiment and theory. Issue 47 (3rd October 2019) - Bellili, A.; Gouid, Z.; Gazeau, M. C.; Bénilan, Y.; Fray, N.; Guillemin, J. C.; Hochlaf, M.; Schwell, M.
Abstract : Methyl isocyanide, CH3 NC, is a key compound in astrochemistry and astrobiology. Abstract : Methyl isocyanide, CH3 NC, is a key compound in astrochemistry and astrobiology. A combined theoretical and experimental investigation of the single photon ionization of gas phase methyl isocyanide and its fragmentation pathways is presented. Vacuum ultraviolet (VUV) synchrotron radiation based experiments are used to measure the threshold photoelectron photoion coincidence (TPEPICO) spectra between 10.6 and 15.5 eV. This allowed us to experimentally determine the adiabatic ionization energy (AIE) and fragment ion appearance energies (AE) of gas-phase methyl isocyanide. Its AIE has been measured with a precision never achieved before. It is found to be AIEexp = 11.263 ± 0.005 eV. We observe a vibrational progression upon ionization corresponding to the population of vibrational levels of the ground state of the methyl isocyanide cation. In addition, four fragment ion appearance energies (AEs) were measured to be AE ( m / z 40) = 12.80 ± 0.05 eV, AE ( m / z 39) = 13.70 ± 0.05, AE ( m / z 15) = 13.90 ± 0.05 eV, AE ( m / z 14) 13.85 ± 0.05 eV, respectively. In order to interpret the experimental data, we performed state-of-the-art computations using the explicitly correlated coupled cluster approach. We also considered the zero-point vibrational energy (ZPVE), core-valence (CV) and scalar relativistic (SR) effects. The results of theoretical calculations of the AIE and AEs are in excellent agreement with the experimental findings allowing for assignment of the fragmentations to the loss of neutral H, H2, CN and HCN upon ionization of CH3 NC. The computations show that in addition to the obvious bond breakings, some of the corresponding ionic fragments result from rearrangements – upon photon absorption – either before or after electron ejection.